Enteroliths in Crohn’s disease - Miłek, Tomasz; Ciostek, Piotr; Woźniak, Witold; Respondek, Wioletta; Jarosz, Mirosław (Gastroenterology Review/Przegląd Gastroenterologiczny, 2013)
A 50-year-old woman was admitted to the Gastroenterology Department for macrocytic anaemia. The patient had attacks of strong abdominal pain. On ultrasonography an approximately 15 cm long intestinal loop with loss of haustrations was visualised medially to the ascending colon. An abdominal X-ray was obtained and visualised oval opacifications with calcium saturated halos within the small pelvis. These opacifications were located within the lumen of the small bowel. The X-ray demonstrated the presence of isolated fluid levels within the small bowel. A colonoscopic examination was performed, where the image of the ascending colon and caecum mucosa suggested Crohn’s disease. Gastroscopy revealed two healing ulcers within the duodenal ampulla, with signs of unspecific inflammations on the histopathological examination of the biopsy specimens. During the hospitalisation severe pain and features of gastrointestinal subobstruction occurred. The surgery revealed two intestinal loops adhering side to side 30 cm from the caecum. Their close adherence caused intestinal obstruction. Numerous stones were palpable. Segmental resection of the ileum along with the intestinal conglomerate was performed. Continuity of the gastrointestinal tract was recreated by stapling the intestinal endings side to side. A developing fistula was found between intestinal loops. Histopathological examination revealed changes characteristic of Crohn’s disease.